SARS-CoV-2 infection and COVID-19 in asthmatics: a complex relationship - Skevaki, Chrysanthi; Karsonova, Antonina; Karaulov, Alexander; Fomina, Daria; Xie, Min; Chinthrajah, Sharon; Nadeau, Kari C.; Renz, Harald (Nature reviews. Immunology, 2021)
Risk of severe coronavirus disease 2019 (COVID-19) after infection with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is increased in patients with certain comorbidities, including chronic obstructive pulmonary disease (COPD). By contrast, epidemiological data from many (but not all) countries indicate a low prevalence of asthma among patients with severe COVID-19. This reduced risk of severe COVID-19 may apply specifically to patients with the type 2 asthma endotype, which is most common in childhood asthma. Somewhat surprisingly, individuals with asthma do not seem to have a greater risk of developing severe COVID-19. Here, the authors offer mechanistic insights to explain the epidemiological data.